Cyber resilience revisited: Law and international relations - Ika Riswanti Putranti; Marten Hanura; Safrida Alivia Sri Ananda; Gawinda Nura Nabila (Universitas Negeri Yogyakarta, 2022)
Cyber space is increasingly playing an important role in the global world, affecting the pattern of relations between countries. The issue of non-traditional security threats is shifting towards the threat typology associated with cyber space. The concept of national security began to be complemented by a national cyber security strategy to support the security of its national interests. Where the country needs to ensure the security of cyber ecosystems to maintain national economic stability. The large flow data and information increasingly large and complex, and brings hidden costs in the form of cyber security threats. Cyber security concepts that are considered not responsive and resilient in dealing with and overcoming cyber attacks can occur at any time with patterns and types that continue to evolve. The concept of cyber security should begin to be developed into cyber security that has patterns of recovery, adaptation, and evolution so as to be able to answer the dynamics of challenges in international trade. Interrupted cyber systems in international sphere will potentially cause disruption of international relations because the threat of losses caused not only affects one country. The increasingly complex international law context and involving big data should be one of the top priorities for cyber resilience strategies. This paper starts by explaining the state of play of cyber resilience in international relations and law. Next, analysis why the concept of cyber resilience in the perspective of international relations and international law needs to be re-visited to face challenges in the digital economy.